(3GdehLRs - (3YdGA GdOjf, Ydj Hf CHi GdMRe GdbQTi , GHf GdfajSs; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s ((3eMeO GHf Ydi Tjf s)
(3ChdgG (B:s
(3bGd GdTjN CHh GdMSf YdGA GdOjf Hf QJHJ gPG GdcJGH Ydi CQHYI afhf s
(3BNQgG (B:s
(3hGSJYedhG OhGA LGdjfhS hZjQg ef GdYdGL GdePchQ hef gGgfG fNJe GdcJGH s
(3fSNI KGfjI ePgHI GdWGdYs
(3hYdjgG NW Rjf YHOGdhGMO GdWjH GdESQGFjdis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdWHs